Automatic Feeding System for Fish Using Fuzzy Logic Method - Sevril Anugrah K Surbakti; Cindy Arditha Claudia Manurung; Mohammad Hafiz Fachrezi Lubis; Zakaria Hidayatullah; Rahiim Tahajjadan Zhaahir Haq Haq; Nanda Octavia; Ivan De Nerol (Batrisya Education, 2025)
This investigate presents an inventive approach to upgrade angle cultivating hones through the usage of an Programmed Bolstering Framework utilizing Fluffy Rationale. The proposed framework points to optimize the bolstering handle by considering components such as water temperature, water quality, and the time of the past nourishing. Fluffy rationale calculations are utilized to create brilliantly choices with respect to the amount of nourish, sort of bolster, ideal nourishing time, and the in general wellbeing status of the angle. The system's flexibility to changing natural conditions makes it a profitable device for economical aquaculture hones.